2022
DOI: 10.3390/diagnostics12112687
|View full text |Cite
|
Sign up to set email alerts
|

CD8 Encephalitis: A Diagnostic Dilemma

Abstract: CD8+ encephalitis is a subacute encephalopathy associated with HIV infection. Pathophysiology is thought to be auto-reactive CD8+ cells attacking on HIV infected CD4+ cells and ‘viral escape’ phenomena (replication of CD8+ cells in CSF). We present a case of a 45-year-old man with well controlled HIV who developed CD8 encephalitis following Herpes simplex encephalitis. He had persistent encephalopathy for several weeks with status epilepticus and agitated delirium, and diagnosis remained elusive until a brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Because brain parenchyma lacks resident T-cells, brain CD8+ T-cell infiltration is considered an autoimmune etiology of brain disease [ 15 , 45 ]. Several reports have shown that it occurs in several encephalitic syndromes, including infections such as HIV CD8+ encephalitis [ 14 , 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because brain parenchyma lacks resident T-cells, brain CD8+ T-cell infiltration is considered an autoimmune etiology of brain disease [ 15 , 45 ]. Several reports have shown that it occurs in several encephalitic syndromes, including infections such as HIV CD8+ encephalitis [ 14 , 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…AIE presents a diagnostic challenge as an inflammatory brain disease, with relatively few reported cases in the literature that have undergone brain biopsy or autopsy [ 4 , 12 ]. Recently, a distinct form of CNS immune reconstitution inflammatory syndrome (IRIS) known as ‘CD8 encephalitis’ has been recognized [ 14 , 15 ]. This condition is characterized by the infiltration of CD8+ T cells into the brain in the absence of a high viral burden or typical IRIS presentation.…”
Section: Introductionmentioning
confidence: 99%
“…This encephalitis presents with an acute onset of headache, encephalopathy, seizure, or coma and more commonly affects females. CD8+ encephalitis is a result of an autoimmune attack on the brain via CD8+ T cells, and it is more likely to result in death than HIV encephalitis [ 76 , 77 , 78 ]. In CD8+ encephalitis, perivascular white matter lesions and other diffuse white matter changes with possible cerebral edema are seen on most MRIs [ 78 ].…”
Section: Glutathione In Hiv-associated Dementia (Hiv Encephalitis)mentioning
confidence: 99%